Compliance With Health-related Behaviors in Mothers of Hospitalized Children in Kashan, Iran: A Cross-Sectional Study - Zahra Kachoee-Bidgoli; Ali Hajibagheri; Ismail Azizi-Fini; Fateme Atoof (Iran University of Medical Sciences, 2022)
Introduction & Objective: Parents' understanding of how to prevent diseases and treat them promptly is an influential factor in a child's development. Thus, adherence to health-related behaviors depends on the awareness and performance of mothers. In any society, mothers and children require much more health care than other age groups because of their vulnerability. As a result, they draw special attention to themselves. Paying attention to children in a community is an investment in its long-term future. Therefore, it is particularly important to prevent, diagnose, and treat diseases in childhood. In addition, one of the most important aspects of disease prevention for children is observing a mother's behavior with regard to the health of her child. Mothers and children are always a priority group in any society. This is because they are not only the primary consumers of healthcare services but also a large group of vulnerable individuals. This implies that healthy behaviors are essential to maintaining and improving the health of children, families, and society. Furthermore, mothers play a significant role in maintaining and enhancing the health of their children. In order to examine the behaviors associated with the health of hospitalized children and related factors among mothers of hospitalized children, the researchers conducted the present study. Materials and methods:This study was a cross-sectional study conducted by observing the behavior of 216 mothers with children who were hospitalized in children's wards of educational hospitals affiliated with Kashan University of Medical Sciences from November 2018 to March 2019. Based on the preliminary study results, the sample size was calculated by taking the average score of the questionnaire, 20.3 ± 4.75, the first type error of 5%, and the estimation error of 0.5 based on the formula of 216 people. In this study, sampling was continuous. After obtaining permission from the hospital and department officials, the second author visited two educational-therapeutic centers' children's departments. Then, among the hospitalized patients (children), he selected those children whose mother was at the hospital as the primary caregiver. They were then apprised of the objectives of the research, and their hygiene behavior would be observed in the following stages. Afterward, they were asked to provide written consent for participation in the study. In the next stage, the first author (who was a member of the children's department in both study centers) observed the mothers' health behaviors toward their children indirectly. As soon as the observer saw the mother's intrusive behavior in the ward, he immediately went to the nursing station to document it. Due to the fact that the observer was a member of the nursing staff, the possibility of altering the mother's behavior was reduced. Each mother observed the behaviors for nearly 8 hours. In most cases, data collection took place during the morning and evening shifts. The first researcher informed the second researcher of the presence of the mother at the child's bedside by asking the mother of the child. It is likely that the first researcher will also be on shift if a mother is present at the child's bedside during the evening or night shifts. Two parts of a demographic and clinical information questionnaire were used in this study. In order to assess the child's health behaviors, a checklist was used. Data were collected and then analyzed using SPSS v16 software (SPSS Inc., Chicago, IL, USA). We used descriptive statistics, pearson correlation, one-way ANOVA, independent t-test and linear regression analysis to analyze the data. Findings:This study examined 216 mothers of children in the children's ward, 11 of whom were excluded as more than one-third of the items related to the child's health-related behavior questionnaire (more than 11 items) did not apply to them. As a result, they were removed from the data, and the analyses presented here were conducted on 205 individuals. According to the present study, the average age of the mother and father of hospitalized children was 29.27±5.60 and 33.61±6.03 years, respectively. Bachelor's degrees are most common among mothers (31.7%), while diploma degrees are most common among fathers (37.6%). About 91% of mothers are homemakers, and 43% of fathers are workers. The average age of children was 12.16±6.43 months, and more than 80% of them were born first or second. Fever and gastroenteritis accounted for 30.7% of all children who were hospitalized. Based on the study's results, the mean score for observing the health behaviors of mothers of hospitalized children was 16.73±5.55. According to the study, the items "use fresh and safe water for the child to drink" (97.5%), "wash hands with soap and water if they become contaminated with clear water" (95.6%), "Change clothes and bedding as soon as they become contaminated with diarrhea, vomit, blood, and other contaminants" (90.7%), and "Wash hands after changing the child's diaper" (87.3%) had the highest compliance rates. It was found that the items "washing hands before changing a baby's diaper" (8%), "keeping the mobile phone covered with a plastic cover to prevent contamination" (8.8%), "washing hands after contact with the surrounding environment" (15.8%) and "hand washing before breastfeeding the child" (16.7%) had the lowest level of compliance by mothers. Moreover, the results of the multiple linear regression test showed a positive and significant correlation between the average child's health-related behavior compliance score and the mother's age (P=0.000; r=0.157). Conclusion:The results indicate that mothers failed to comply with behaviors such as washing their child's hands regularly and washing their own hands before feeding their children. It is necessary to educate and inform mothers regarding the observation of behaviors related to the child's health upon entering the hospital in order to ensure their child's safety. In hospitals, it is, therefore, necessary for educational supervisors, patient education supervisors, and children's department supervisors to devise and implement special programs aimed at informing mothers of the importance of protecting their children during hospitalization by educating them about health behaviors.